PENGARUH KELOMPOK REFERENSI DAN GAYA HIDUP TERHADAP KEPUTUSAN PEMBELIAN GEN Z DI COFFEE SHOP “JANJI JIWA” PADANG - Vonni Amelia; Juarsa Badri (Jurnal Bina Bangsa Ekonomika, 2024)
This study aims to investigate the influence of Reference Groups and Lifestyle on the Purchase Decisions of Generation Z at "Janji Jiwa" Coffee Shop in Padang. The focus is to provide a deep understanding of the factors affecting the preferences and purchasing behavior of Generation Z in the context of a coffee shop. The research method employs a quantitative approach with a survey design. The sample consists of 96 respondents from Generation Z who are visitors to "Janji Jiwa" Coffee Shop at Jl. Batang Arau No.60, Berok Nipah, Padang. Data were collected through questionnaires and data analysis was performed using multiple regression tests to assess the influence of the independent variables on the dependent variable. The results indicate that both Reference Groups and Lifestyle significantly and positively influence the Purchase Decisions of Generation Z at "Janji Jiwa" Coffee Shop in Padang